2018
DOI: 10.1186/s40645-018-0170-0
|View full text |Cite
|
Sign up to set email alerts
|

Multi-instrumented observations of the equatorial F-region during June solstice: large-scale wave structures and spread-F

Abstract: Typical equatorial spread-F events are often said to occur during post-sunset, equinox conditions in most longitude sectors. Recent studies, however, have found an unexpected high occurrence of ionospheric F-region irregularities during June solstice, when conditions are believed to be unfavorable for the development of plasma instabilities responsible for equatorial spread-F (ESF). This study reports new results of a multi-instrumented investigation with the objective to better specify the occurrence of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…One of the top research priorities in the global space weather community is to better understand the generation mechanisms and the dynamic features of EPBs, because they can severely disrupt the amplitude and phase of transionospheric radio waves so as to cause adverse effects on relevant communication and navigation systems. In addition, the altitudinal information of irregularities embedded within EPBs can be examined through observations of plume-like structures from coherent backscatter radar or incoherent scatter radar measurements (Ajith et al, 2015;Jin et al, 2018;Li et al, 2013;Rodrigues et al, 2018;Tulasi Ram et al, 2017;Yokoyama & Fukao, 2006). During quiet times, the prereversal enhancement (PRE) of the zonal electric field is responsible for the enhanced upward E × B drift after sunset, which elevates the ionospheric height and subsequently amplifies the growth rate of R-T The morphological features and spatial/temporal variability of EPBs have been widely investigated via case studies and statistical analysis using different observational methods.…”
Section: Introductionmentioning
confidence: 99%
“…One of the top research priorities in the global space weather community is to better understand the generation mechanisms and the dynamic features of EPBs, because they can severely disrupt the amplitude and phase of transionospheric radio waves so as to cause adverse effects on relevant communication and navigation systems. In addition, the altitudinal information of irregularities embedded within EPBs can be examined through observations of plume-like structures from coherent backscatter radar or incoherent scatter radar measurements (Ajith et al, 2015;Jin et al, 2018;Li et al, 2013;Rodrigues et al, 2018;Tulasi Ram et al, 2017;Yokoyama & Fukao, 2006). During quiet times, the prereversal enhancement (PRE) of the zonal electric field is responsible for the enhanced upward E × B drift after sunset, which elevates the ionospheric height and subsequently amplifies the growth rate of R-T The morphological features and spatial/temporal variability of EPBs have been widely investigated via case studies and statistical analysis using different observational methods.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the dominant periodicity of 25/28.5 day in vernal/autumnal equinox season was similar in ionospheric S4 and the geomagnetic parameters. Recent investigation based on continuous observations over successive days has indicated a close relationship between the ionospheric irregularities observed using the Jicamarca radar and the auroral electrojet (Rodrigues et al, 2018). Such a relationship is not limited to a few intense geomagnetic storms.…”
Section: 1029/2018ja026419mentioning
confidence: 99%
“…For this night we can directly observe that there are concurrent airglow depletions and small-scale irregularities, but recently Rodrigues et al (2018) showed that airglow signatures can occur before post-midnight irregularities. In the ASI images from this night, depletions in the entire field of view are only visible after 04:00 UT yet there are large plumes of irregularities visible in the RTI plots earlier.…”
Section: Coherent Scatter Radar and Asi Comparisonmentioning
confidence: 99%
“…We do not expect other undulations to move in the same way and have the same extent and shape in the field of view. Precursors to post-midnight ESF as described in Rodrigues et al (2018) show airglow structures that are not associated with ESF and are likely due to LSWS. Equatorial spread F structures tend to move with regular motion eastward and the precursors Rodrigues et al (2018) had very little motion, often staying in the same location for multiple images.…”
Section: Depletion Patterns and Morphologymentioning
confidence: 99%
See 1 more Smart Citation